PENGUATAN KARAKTER DAN PRESERVASI PENGETAHUAN MELALUI PEMBACAAN PRASASTI: STUDI PEMBACAAN PRASASTI DADIA ARYA DALEM TARUKAN - Ariyani, Luh Putu; Tantri, Ade Asih Susiari (ACARYA PUSTAKA, 2017)
The purpose of education in Hinduism is to establish an adult human or dewasa (dewasa= human with god character). Education is also an attempt to achieve Catur Purusa Arta (the four goals of human life). Having enough knowledge will help people build good characters. Strengthening the human characters are not only trained in the school but also in the family environment. Balinese tradition in transferring moral messages for the younger generation is very diverse. One of them is through the reading "prasasti" on certain clans in Bali. Prasasti is lontar (palm-leaf manuscript) contained a genealogy or a chronicle of a clan. âPrasastiâ is usually read once every 210 days. All members of the clan will gather at the family temple to listen to the messages which inherited by their ancestors. Knowing the chronicle of the family is very important for Balinese in order to increase pride and self-esteem. In this event, youth would learn how important to be good people. At the end of the reading, the elders will give commentary to the text in order to be imitated by future generations. In the context of library science,Â  Balinese are familiar with the information literacy as a means to pass on the knowledge from generation to generation in order to pass on the noble values that have been handed down. This paper tries to explore: (1) why some clans still maintain the tradition of reading âprasastiâ, while there are clans that did not;Â  and (2) what values are presented at the time of reading âprasastiâ.Â Keywords: prasasti, lontar, character strengthening, information literacy